1994
DOI: 10.1103/physrevlett.72.2130
|View full text |Cite
|
Sign up to set email alerts
|

Effective kink-kink interaction in a one-dimensional model mediated by phonon exchange

Abstract: The general 1D double-well model with anharmonic interaction is considered in the displacive limit.Expansion of the Hamiltonian around a multikink state results in a phonon-kink Hamiltonian. lt is shown that at rather low temperatures and short wavelengths the phonon-kink interaction can be treated in Born approximation, leading to a decomposition of the multikink-phonon Hamiltonian. Elimination of the phonons results in an eA'ective potential for the kink-kink interaction, which corresponds to the one-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Wada and co-workers [11] examined the nonlinear interaction between solitary excitations and linear oscillating modes of the sine-Gordon equation, and, as a result of the coupling, they found diffusive motion of the former. Quite 0953-8984/96/224031+14$19.50 c 1996 IOP Publishing Ltd similarly, Rostiashvili and Schilling [12] showed that the coupling of domain walls to spatial fluctuations of the magnetization leads to an effective kink-kink interaction. Here we investigate the coupling of the sine-Gordon field to the surrounding lattice vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Wada and co-workers [11] examined the nonlinear interaction between solitary excitations and linear oscillating modes of the sine-Gordon equation, and, as a result of the coupling, they found diffusive motion of the former. Quite 0953-8984/96/224031+14$19.50 c 1996 IOP Publishing Ltd similarly, Rostiashvili and Schilling [12] showed that the coupling of domain walls to spatial fluctuations of the magnetization leads to an effective kink-kink interaction. Here we investigate the coupling of the sine-Gordon field to the surrounding lattice vibrations.…”
Section: Introductionmentioning
confidence: 99%